Creative response activities for children on the spectrum a therapeutic and educational memoir - Henley, David (David R.) (New York Routledge, 2018)
Creative Response Activities for Children on the Spectrum is a clear, comprehensive and intuitive guide that offers a wide selection of hands-on interventions to be used in any therapeutic or educational setting with children who are ‘on the spectrum’. From drawing and writing poetry to skiing and skateboarding, this book describes these and many other creative activities geared towards children with autistic features, attention deficits, hyperactivity, paediatric bipolar disorder and other related conditions. This new resource provides an innovative blend of theory and illustrative case examples designed to help therapists and educators assess children’s needs, formulate therapeutic and aesthetic interventions, and analyze creative outcomes.--Provided by publisher.
Keywords: Autism in children -- Treatment; Autistic children -- Care